O05.4 The effect of the combined oral contraceptive pill on the vaginal microbiota of women treated for bacterial vaginosis. (14th July 2019) - Ratten, Larissa; Bradshaw, Catriona; Plumer, Erica; Fairley, Christopher; Murray, Gerald; Garland, Suzanne; Danielewski, Jennifer; Tachedjian, Gilda; Chow, Eric; Vodstrcil, Lenka
Abstract : Background: Bacterial Vaginosis (BV) is considered to be a dysbiosis of the vaginal microbiota (VM); it causes vaginal symptoms, increases risk for STI/HIV acquisition and negatively impacts obstetric outcomes. We analysed the VM of women from an open-label trial of women randomized to the combined-oral contraceptive pill (COCP) or current non-hormonal contraceptive practices after antibiotic treatment for BV. Our aim was to determine if COCP-exposure was associated with an optimal VM dominated by Lactobacillus spp. following antibiotic treatment. Methods: Women (N=92) returned vaginal swabs and questionnaires monthly for 6 months or until BV recurrence. Specimens (N=449) underwent VM analysis by 16S rRNA gene V3V4 amplicon sequencing. Alpha diversity was calculated using the Shannon diversity index. Associations between behavioural factors and diversity were investigated using generalized estimating equations population-averaged models and multinomial regression was used to assess factors associated with composition. Results: Specimens were grouped into five VM types: Lactobacillus iners dominated, L. crispatus dominated, mixed Lactobacillus spp., Gardnerella vaginalis dominated and mixed highly diverse taxa. COCP-exposure was associated with a decrease in VM diversity (Shannon; adjusted coefficient=-0.55, 95%CI:-0.75, 0.36, p<0.001). Women with COCP-exposure were also more likely to have VM dominated by either L. iners (adjusted relative risk ratio [RRR]=4.40, 95%CI: 1.90, 10.18, p=0.001) or L. crispatus (adjRRR=3.12, 95%CI:1.24, 7.81, p=0.015) than one dominated by G. vaginalis . Conversely, women who reported an ongoing regular sex partner (RSP) were more likely to have a VM dominated by G. vaginalis (adjRRR=2.56, 95%CI:0.80, 8.22, p=0.144) or mixed diverse taxa (adjRRR=2.01, 95%CI:0.81, 4.99, p=0.129) than by L. crispatus, although this was not significant. Conclusion: COCP-exposure is associated with higher relative abundance of Lactobacillus spp. and an increased likelihood of developing a VM dominated by L. crispatus or L. iners following antibiotic treatment. Conversely, re-exposure to an RSP increased the likelihood of a VM that was abundant in BV-associated bacteria including G. vaginalis . These findings have important implications for the development of BV treatment and prevention strategies. Disclosure: No significant relationships.